Vascular complications in craniopharyngioma-resected paediatric patients: a single-center experience - Castelli, Barbara; Scagnet, Mirko; Mussa, Federico; Genitori, Lorenzo; Sardi, Iacopo; Stagi, Stefano (Frontiers in Endocrinology, 2024)
Background: Craniopharyngioma (CP), although slow growing and histologically benign, has high morbidity, mostly related to hypothalamus-pituitary dysfunction and electrolyte imbalance. Increased risk of vascular complications has been described. However, data are still poor, especially in the paediatric population. The aim of our study was to evaluate the occurrence, timing, and predisposing factors of deep venous thrombosis (DVT) and other vascular alterations in neurosurgical paediatric CP patients. Material and Methods: In a single-center, retrospective study, we investigated 19 CP patients (11 males, 8 females, mean age 10.5±4.3 years), who underwent neurosurgery between December 2016 and August 2022, referred to Meyer Children's Hospital IRCCS in Florence. Results: Five patients (26.3%) presented vascular events, which all occurred in connection with sodium imbalances. Three DVT (two with associated pulmonary embolism, in one case leading to death) developed in the post-operative period, most frequently at 7-10 days. Elevated D-dimers, a reduced partial activated thrombin time and a prolonged C-reactive protein increase were highly related to thrombotic vascular events. One case of posterior cerebral artery pseudoaneurysm was described soon after neurosurgery, requiring vascular stenting. Superficial vein thrombophlebitis was a late complication in one patient with other predisposing factors. Conclusion: CP patients undergoing neurosurgery are at risk of developing DVT and vascular alterations, thus careful follow-up is mandatory. In our study, we found that the phase of transition from central diabetes insipidus to a syndrome of inappropriate antidiuretic hormone secretion may be a period of significant risk for DVT occurrence. Careful vascular follow-up is mandatory in CP-operated patients.